1997
DOI: 10.1001/jama.1997.03540320082047
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Empathic Communication in the Medical Interview

Abstract: This empirically derived model of empathic communication has practical implications for clinicians and students who want to improve their communication and relationship skills. Based on our observations, the basic empathic skills seem to be recognizing when emotions may be present but not directly expressed, inviting exploration of these unexpressed feelings, and effectively acknowledging these feelings so the patient feels understood. The frequent lack of acknowledgment by physicians of both direct and indire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
254
0
5

Year Published

2000
2000
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 579 publications
(270 citation statements)
references
References 23 publications
11
254
0
5
Order By: Relevance
“…An analysis of the oncologists' behaviors in the recordings used in this study is reported elsewhere; in that analysis, oncologists responded empathically to patients' expressions of emotion less than one third of the time [42]. Research shows that when clinicians repeatedly miss patients' expressions of emotion, patients eventually cease to express emotion [56]. As the majority of the patients in our recorded conversations knew their oncologist, it may be that the patients "learned" not to express emotion by the time they were recorded.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…An analysis of the oncologists' behaviors in the recordings used in this study is reported elsewhere; in that analysis, oncologists responded empathically to patients' expressions of emotion less than one third of the time [42]. Research shows that when clinicians repeatedly miss patients' expressions of emotion, patients eventually cease to express emotion [56]. As the majority of the patients in our recorded conversations knew their oncologist, it may be that the patients "learned" not to express emotion by the time they were recorded.…”
Section: Discussionmentioning
confidence: 97%
“…Based on previous work [6,34,56], we defined negative emotional expression as any instance where a patient used words to describe a negative emotional state in the past, present, or future; for example, "I'm anxious about this test" or "I was feeling depressed." We identified all instances of verbal expression of negative emotion using a web-based coding software (ENCOUNTER) that allowed direct coding on the audio files.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations